2020
DOI: 10.1007/s11769-020-1114-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal Heterogeneity of Green Development Efficiency and Its Influencing Factors in Growing Metropolitan Area: A Case Study for the Xuzhou Metropolitan Area

Abstract: This study analyzed the spatial-temporal heterogeneity of green development efficiency and its influencing factors in the growing Xuzhou Metropolitan Area for the period 2000-2015. The slacks-based measure (SBM) model, spatial autocorrelation, and the geographically weighted regression (GWR) model were used to conduct the analysis. The conclusions were as follows: first, the overall efficiency of green development of the Xuzhou Metropolitan Area decreased, the regional differences and spatial agglomeration shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Secondly, as for the research on the influencing factors of IGDE, some studies focused on the role of space [ 46 ], but few studies adopted the MGWR model to explore the degree and direction of influence of influencing factors on different units. Through research, this paper found that the scale of impact of different variables on the IGDE is quite different.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, as for the research on the influencing factors of IGDE, some studies focused on the role of space [ 46 ], but few studies adopted the MGWR model to explore the degree and direction of influence of influencing factors on different units. Through research, this paper found that the scale of impact of different variables on the IGDE is quite different.…”
Section: Discussionmentioning
confidence: 99%
“…In order to alleviate the contradiction between man and earth, we must understand the relationship between human activities and GUEUCL. According to the existing literature and research, this paper studies the driving factors of spatial differentiation of green use efficiency of urban construction land in Jilin Province from three aspects: social economic factors, natural science and technology factors, and urban development factors [24][25][26][27][28][29][30][31][32][33].…”
Section: Driving Factors Of Green Utilization Efficiency Of Urbanmentioning
confidence: 99%
“…Land is a complex system of socioeconomic-natural environment, and the efficiency of traditional urban construction land use is limited from the socioeconomic perspective, ignoring the green development concept of land use efficiency following the principle of coordination of economic, social, and ecological benefits. erefore, in the current background of urban sprawl, resource waste and environmental pollution and ecological civilization construction require "green development," and the GUEUCL has attracted wide attention of the state and society [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Because the DEA method does not need dimensionless processing of data, nor any weight assumption and strong objectivity, it has been more recognized and applied in the academic circle. For example, Qiu et al used the Slack Based Model (SBM) model, spatial autocorrelation, and geographically weighted regression model to analyze the spatio-temporal heterogeneity and influencing factors of green development efficiency in the Xuzhou metropolitan area of China ( 14 ). Zhang et al, Shao et al, and He et al researched green transformation from the perspective of total factor productivity by constructing the DEA model ( 15 – 17 ).…”
Section: Introductionmentioning
confidence: 99%